Slip and No Slip Conditions in Serpentine Channel for Bingham Fluid-Numerical CFD Investigation - Panwar, Kuldeep (Journal of Graphic Era University, 2023)
For the flow of a Bing-ham fluid in a serpentine tube with a circular cross section, a numerical examination of slip and no slip scenarios was conducted. This was done in order to better understand the flow. This investigation was carried out. In order to get a deeper comprehension of the flow behavior, several flow situations, including slip and no slip, are investigated using separate sets of parameters. In order to solve the issue presented by the turbulent model, the K-model is put to use. It was discovered that the parameter variation for no slip circumstances is preferable to that of no slip scenarios under high stress. This was discovered by comparing the two. A limited analysis of the flow behavior of the Bingham fluid in a serpentine cannel served as the impetus for the current work. The research that was done was motivated by this analysis.